The need for, and utilization of prostate-bed radiotherapy after radical prostatectomy for patients with prostate cancer in British Columbia - Tyldesley, Scott; Peacock, Michael; Morris, James W; So, Alan; Kim-Sing, Charmaine Kim-Sing; Quirt, Jill Quirt; Carter, Michael; Pickles, Tom (Canadian Urological Association Journal, 2012)